Dampak Resiliensi Finansial, Makroekonomi, dan Leverage terhadap Harga Saham Syariah Indonesia di Jakarta Islamic Index (JII) Tahun 2020–2022 - Rio Duana Putra; Hwihanus Hwihanus (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
The purpose of this study is to determine and evaluate the impact of leverage, macroeconomic conditions, and financial resilience on the price of Indonesian sharia stocks listed on the Jakarta Islamic Index (JII) during COVID-19 in 2020–2022. This study took a quantitative approach to its methodology. Purposive sampling is the method used to acquire the data, and 19 companies registered with JII between 2020 and 2022 comprise the total. The PLS-SEM method was used to conduct the test, and Smart PLS 3.0 statistical software was used. The study's findings demonstrate that leverage, macroeconomics, and financial resilience all have a negative impact on stock prices.